2022
DOI: 10.1371/journal.pone.0266319
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR inhibitor Rapamycin protects from premature cellular senescence early after experimental kidney transplantation

Abstract: Interstitial fibrosis and tubular atrophy, a major cause of kidney allograft dysfunction, has been linked to premature cellular senescence. The mTOR inhibitor Rapamycin protects from senescence in experimental models, but its antiproliferative properties have raised concern early after transplantation particularly at higher doses. Its effect on senescence has not been studied in kidney transplantation, yet. Rapamycin was applied to a rat kidney transplantation model (3 mg/kg bodyweight loading dose, 1.5 mg/kg … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…There are, however, situations not widely recognizable (e.g., enhanced senescence of the graft followed by tubular atrophy and interstitial fibrosis) that lead to chronic allograft dysfunction. Experimental studies have shown that inhibition of inflammatory infiltration by macrophages and CD8+ lymphocytes and reduction in proinflammatory cytokines, such as monocyte chemoattractant protein-1 (MCP-1), IL-1b, and TNF-a, with the use of mammalian/mechanistic target of rapamycin (mTOR) inhibitors, may prevent the emergence of phenotypic changes linked to senescence and chronic graft dysfunction [64].…”
Section: Can Successful Renal Transplantation Reinstate the Immune Pr...mentioning
confidence: 99%
“…There are, however, situations not widely recognizable (e.g., enhanced senescence of the graft followed by tubular atrophy and interstitial fibrosis) that lead to chronic allograft dysfunction. Experimental studies have shown that inhibition of inflammatory infiltration by macrophages and CD8+ lymphocytes and reduction in proinflammatory cytokines, such as monocyte chemoattractant protein-1 (MCP-1), IL-1b, and TNF-a, with the use of mammalian/mechanistic target of rapamycin (mTOR) inhibitors, may prevent the emergence of phenotypic changes linked to senescence and chronic graft dysfunction [64].…”
Section: Can Successful Renal Transplantation Reinstate the Immune Pr...mentioning
confidence: 99%
“…Taken together, these findings suggest that Rapalink-1, by inhibiting the activation of NF-kB, P38, ERK, and 4EBP1, alleviated Lamin B1 expression and suppressed the expression of P21. Previous studies have shown that blocking the activation of NF-κB, MAPKs, and mTOR can dampen senescence in various cell types in vivo and in vitro [17][18][19]. The accumulation of senescent cells has been observed in atherosclerotic lesions [6,7,13].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SASP factors is regulated by MAPKs and mediated through NF-kB transcriptional activity [14]. Blocking NF-κB, MAPKs, and mTOR could inhibit cellular senescence and SASP and increase life span [15][16][17][18][19]. Moreover, activation of these pathways has been implicated in cardiovascular diseases, including atherosclerosis and IAs [15,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…By inhibiting the mTOR pathway, rapamycin may modulate these cellular processes and even reduce the appearance of new senescent cells by promoting homeostasis via the removal of dysfunctional proteins and aged organelles through autophagy. Rapamycin has also been shown to reduce the SASP [67][68][69] to inhibit the production of pro-inflammatory molecules and their signaling pathways. Through an mTOR-dependent reduction in NF-κB transcriptional activity, rapamycin can inhibit the translation of inflammatory SASP factors [40].…”
Section: Rapamycinmentioning
confidence: 99%